STAU1 binds to IBDV genomic double‐stranded RNA and promotes viral replication via attenuation of MDA5‐dependent β interferon induction. Issue 1 (6th July 2018) - Ye, Chengjin; Yu, Zhaoli; Xiong, Yiwei; Wang, Yu; Ruan, Yina; Guo, Yueping; Chen, Mianmian; Luan, Shilu; Zhang, Enli; Liu, Hebin
ABSTRACT: Infectious bursal disease virus (IBDV) infection triggers the induction of type IIFN, which is mediated by melanoma differentiation‐associated protein 5 recognition of the viral genomic double‐stranded RNA (dsRNA). However, the mechanism of IBDV overcoming the type I IFN antiviral response remains poorly characterized. Here, we show that IBDV genomic dsRNA selectively binds to the host cellular RNA binding protein Staufen1 (STAU1) in vitro and in vivo . The viral dsRNA binding region was mapped to the N‐terminal moiety of STAU1 (residues 1–468). Down‐regulation of STAU1 impaired IBDV replication and enhanced IFN‐β transcription in response to IBDV infection, while having little effect on the viral attachment to the host cells and cellular entry. Conversely, over‐expression of STAU1 but not the IBDV dsRNA–binding deficient STAU1 mutant (469–702) led to a suppression of IBDV dsRNA–induced IFN‐β promoter activity. Moreover, we found that the binding of STAU1 to IBDV dsRNA decreased the association of melanoma differentiation‐associated protein 5 but not VP3 with the IBDV dsRNA in vitro . Finally, we showed that STAU1 and VP3 suppressed IFN‐β gene transcription in response to IBDV infection in an additive manner. Collectively, these findings provide a novel insight into the evasive strategies used by IBDV to escape the host IFN antiviral response.—Ye, C., Yu, Z., Xiong, Y., Wang, Y., Ruan, Y., Guo, Y., Chen, M., Luan, S., Zhang, E., Liu, H. STAU1 binds to IBDV genomic double‐stranded RNA and promotes viral replication via attenuation of MDA5‐dependent β interferon induction. FASEB J. 33, 286–300 (2019). www.fasebj.org